Meningkatkan Kemampuan Memecahkan Masalah Dalam Pembelajaran Akidah Akhlak dengan Model PBL Pada Siswa Kelas VII di MTS Negeri 6 Padang Pariaman Tahun Pelajaran 2021/2022 - Martini Martini (Journal on Education, 2022)
Based on the results of the research above, there are several findings in this classroom action research that can be concluded, namely: 1) The average score of student activities relevant to learning has increased from cycle I to cycle II. In the first cycle of meeting 1, the average score was 60.92 (Uncompleted), the first cycle of the second meeting obtained an average value of 70.80 (Uncompleted), the second cycle of meeting 1 obtained an average value of 79.32 (Uncompleted). Completed), cycle II meeting 2 obtained an average score of 89.92 (Completed), showing a significant increase of 20 points. 2) The average score of student activities that are less relevant in learning has decreased from 17% in the first cycle of the 1st meeting to 0% in the second cycle of the 2nd meeting. It shows the success of the teacher's motivation with PBL. 3) The average score of student test results, in the first cycle of meeting 1 of 64.17 with an average percentage of learning completeness of 42%, the first cycle of meeting 2 obtaining an average value of 73.64 (Not Complete) with an average completeness student learning 46%, cycle II meeting 1 obtained an average score of 83.18 (completed) with an average student learning completeness of 83%, cycle II meeting 2 obtained an average score of 92.73 (completed) with an average completeness 100% student learning showed a significant increase of 28.56 points and 58% for learning completeness. Based on this research, it can be concluded that the Problem Based Learning model can improve students' ability to solve the problem of Akidah Akhlak material in class VII student learning at MTS Negeri 6 Padang Pariaman in the 2021/2022 academic year.